Model Perjanjian Bisnis Kreatif Usaha Mikro, Kecil, Menengah dan Start-Up Berbasis Paid Promote: Era Hyper-Connected Society - Samsithawrati, Putu Aras; Kurniawan, I Gede Agus; Dharmawan, Ni Ketut Supasti (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 03 (2022)DO - 10.24843/AC.2022.v07.i03.p2, 2022)
The purpose of this paper is to elaborate on the agreement model and important clauses related to business development based on paid promotion on social media in the era of a hyper-connected society that is beneficial for all parties. This paper uses a normative legal research method with a statutory, conceptual, and analytical approach. The electronic-based business development agreement model of paid promotion on social media in the era of a hyper-connected society can be categorized as a creative variant of a service agreement. Although the tendency in business development with paid promotion on social media is in the form of standard contracts, in the context of an agreement that is legal, fair, and beneficial for the parties, the characteristics of the paid-promote agreement model become relevant to be stated in the form of agreement clauses. Those are the obligation to upload content, obligation to pay promotion fees, uploaded content, amount of uploaded content, the precise time to upload content, duration of displaying uploaded content, number of followers on social media, price, promotion fees, payment mechanism, period and expiration of paid promote agreement, the event of default, as well as dispute resolution. Accuracy in elaborating the elements of the agreement and their detailed placement in firm clauses leads to legal certainty, expediency, and reduces legal risks, especially for Micro, Small, and Medium Enterprises and start-up businesses who are just starting to develop their business by using paid-promote agreement model in the hyper-connected era as an alternative.